2024
DOI: 10.2147/ijwh.s436222
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal and Interdisciplinary Interventions for the Treatment of Localized Provoked Vulvodynia: A Scoping Review of the Literature from 2010 to 2023

Alex Rains,
Krisztina Bajzak,
Michelle Miller
et al.

Abstract: Localized provoked vulvodynia (LPV) is a chronic condition characterized by pain in the vulvar vestibule, which can be provoked by pressure or touch and which is not tied to a clear underlying cause. Research into the etiology of and most appropriate treatment strategy for LPV is still limited. Methods: Using Arksey and O'Malley's model for scoping reviews, we evaluated the research question: what is the current evidence regarding the efficacy/effectiveness of multimodal or interdisciplinary interventions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 49 publications
(125 reference statements)
0
7
0
Order By: Relevance
“…Most vestibulectomy studies did not specify details of preceding treatments. While the case series discussed in this paper had globally positive results for dyspareunia, studies comparing vestibulectomy with conservative management, discussed in our companion paper, 13 generally reported that dyspareunia outcomes were comparable to multimodal/interdisciplinary therapies, underscoring the importance of comparator groups for this intervention. Lack of comparator groups may have inflated treatment response due to possible spontaneous improvements over time.…”
Section: Dovepressmentioning
confidence: 75%
See 4 more Smart Citations
“…Most vestibulectomy studies did not specify details of preceding treatments. While the case series discussed in this paper had globally positive results for dyspareunia, studies comparing vestibulectomy with conservative management, discussed in our companion paper, 13 generally reported that dyspareunia outcomes were comparable to multimodal/interdisciplinary therapies, underscoring the importance of comparator groups for this intervention. Lack of comparator groups may have inflated treatment response due to possible spontaneous improvements over time.…”
Section: Dovepressmentioning
confidence: 75%
“…Studies that compared physical interventions with pharmacological or psychological interventions were categorized as multidisciplinary/multimodal and are reported elsewhere. 12,13 Laser Therapy…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations